Personal value systems of men and women entrepreneurs versus managers - Fagenson, Ellen A. (Journal of Business Venturing, 1993)
Many have suggested that the type of individual who becomes an entrepreneur is psychologically distinguishable from the type of individual who becomes a manager. Moreover, it has been argued that within these occupations men and women are fundamentally different. This paper discusses a study that evaluated the accuracy of these characterizations by comparing the personal value systems of men and women entrepreneurs and managers. This information should prove useful to a variety of audiences. First, individuals exploring career alternatives can evaluate the appropriateness of entrepreneurial and managerial careers for themselves by determining whether or not their own value systems match those of individuals already in these roles. Second, venture capitalists, bank loan officers, and individuals in organizations who are in positions to support women's entrepreneurial and managerial pursuits will be able to determine whether or not women and men in these roles are “made from the same cloth” and thus deserve the same consideration. Third, the current research will also shed some light on the compatibility of the entrepreneurial and managerial roles, a role transition that entrepreneurs make as their businesses mature. Finally, by studying the values of individuals in these two fields an assessment of the basic nature of these individuals can be made. Two hundred fifty-five men and women entrepreneurs and managers rank-ordered 15 terminal (desired end states) and 15 instrumental (methods used by individuals to achieve desired end states) values using a modified version of the Rokeach (1973) Value Survey. The results of the study revealed that individuals' gender had very little influence on their value systems. Women valued the terminal value of equality more than men, and men valued “family security” more than women. In contrast, managers and entrepreneurs had vastly different value systems. Entrepreneurs gave significantly greater weight than managers to the following terminal values (listed from most to least important): self-respect, freedom, a sense of accomplishment, and an exciting life, and the following instrumental values (listed front most to least important): being honest, ambitious, capable, independent, courageous, imaginative, and logical. In contrast, managers gave greater weight than entrepreneurs to the terminal values of (listed from most to least important): true friendship, wisdom, salvation, and pleasure, and the instrumental values of (listed from most to least important): being loving, compassionate, forgiving, helpful, and self-controlled. The results of the present study suggest that entrepreneurs want something different out of life than managers. Whereas the latter prefer to enjoy the pleasures that life has to offer, entrepreneurs want to be free to achieve and actualize their potential. Overall, it appears that knowing whether an individual is an entrepreneur or a manager appears to be a better indicator of his/her values than knowing whether an individual is male or female. These results suggest that men and women who become entrepreneurs or, alternatively, secure jobs in the management profession, are more similar to members of the opposite sex within their profession than they are to members of their own sex in a complementary profession. These findings suggest that customers, subordinates, superiors, bank loan officers, and venture capitalists—or in other words, anyone who is involved with men and women entrepreneurs or managers—should be careful not to categorize them according to traditional sex-role stereotypes. As was demonstrated here, these stereotypes are not applicable across the board. Moreover, previous research has shown that they can result in sex discriminatory decisions. Finally, once a business is well underway, managing the operation becomes central to its success. The results of the present study suggest that this change in role emphasis may not be satisfying to the entrepreneur, because the value system of individuals who are committed to the managerial role is at odds with the value preferences of entrepreneurs. This may help explain why many entrepreneurs become less interested and motivated in their ventures once the entrepreneurial component of their job is overtaken by the management aspect.